EKSTRAKSI MINYAK KELAPA MURNI DENGAN METODE PENGADUKAN DAN COLD PRESSED - Deni Pranata; Puji Ardiningsih; Winda Rahmalia; Nurlina Nurlina; Intan Syahbanu (Tanjungpura University, 2020)
Virgin coconut oil (VCO) was prepared by stirring and cold-pressed methods. This research aimed to study the effectiveness of both methods on VCO extraction. The first method was carried out by high-speed stirring to broke the coconut milk emulsion, and the second method was using the freezing and thawing technique. The physical appearance of VCO from both ways was clear, with a specific odor and taste of fresh coconut oil. The density of the VCO obtained by the stirring and cold-pressed method was 936 kg/m3 and 933 kg/m3, respectively. Physicochemical characterization shows that the cold-pressed process produces better properties of VCO.